Estudo ecotoxicológico do glufosinato de amônio em Eisenia andrei (Bouché, 1972) - Silva, Rafaela Oliva da (Universidade Federal de São Carlos, 2024)
In the context of the growing use of pesticides, especially glufosinate ammonium, in the face of weed resistance to herbicides and the development of transgenic crops tolerant to glufosinate ammonium, which have significantly increased its importance in agriculture, it is crucial to understand the consequences of its application and its potential threat to ecosystems, particularly terrestrial ecosystems. The species Eisenia andrei is often used in ecotoxicological studies due to its ecological importance in maintaining soil structure and fertility and its sensitivity to contaminants. This study aimed to evaluate the ecotoxicological effects of the herbicide glufosinate ammonium on earthworms of the species Eisenia andrei (Bouché, 1972), focusing on aspects of acute, chronic and behavioral ecotoxicity. The tests were conducted in accordance with International Organization for Standardization (ISO) standards (11268-1, 1993; 11268-2, 1998; 17512-1, 2008). All tests used a completely randomized design (DIC), with six concentrations of the herbicide glufosinate ammonium (acute: 0, 175, 340, 505, 670 and 835 mg i. a. kg-1; chronic and behavioral 0, 3.3; 5; 6.7; 8.3 and 10 mg i.a. kg-1) and four replicates for the acute and chronic tests and five replicates for the behavioral test. The results showed significant impacts on the survival, biomass, reproduction and behavior of the earthworms at certain concentrations. The Median Lethal Concentration (MIC) for 14-day mortality was set at 611.68 mg i.a. kg-1, indicating moderate toxicity to the herbicide. The Median Effective Concentration (MIC) for effects on reproduction in 56 days and for inducing escape in 48 hours were set at 4.49 mg i.a. kg-1 and 3.30 mg i.a. kg-1, respectively. The concentrations of 8.3 and 10 mg i.a. kg-1 induced the greatest escape responses, but did not reach the 80% escape threshold established by ISO 17512-1 for classifying a substance as toxic. These findings highlight the importance of assessing the ecotoxicological risks of pesticides such as glufosinate ammonium for safer and more sustainable agricultural management practices.
Ecotoxicological study of glufosinate ammonium in Eisenia andrei (Bouché, 1972)
Keywords: Contaminação do solo; Herbicida; Minhoca; Oligoqueta; Organismo não alvo; Contaminated soil; Herbicide; Earthworm; Oligochaeta; Non-target organism; CIENCIAS AGRARIAS::AGRONOMIA